Playing with Desire : Christopher Marlowe and the Art of Tantalization - Tromly, Fred B., 1943- (Book collections on Project MUSE., 1998)
"Playing with Desire takes a new approach to Christopher Marlowe's body of writing, replacing the view of Marlovian desire as heroic aspiration with a far less uplifting model. Fred B. Tromly shows that in Marlowe's writing desire is a response to calculated, teasing enticement, ultimately a sign not of power but of impotence. The author identifies this desire with the sadistic irony of the Tantalus myth rather than with the sublime tragedy exemplified by the familiar figure of Icarus. Thus, Marlowe's characteristic mis en scene is moved from the heavens to the netherworld. Tromly also demonstrates that the manipulations of desire among Marlowe's characters find close parallels in the strategies by which his works tantalize and frustrate their audiences."--Jacket